Efficacy and safety of artesunate plus amodiaquine in routine use for the treatment of uncomplicated malaria in Casamance, southern Sénégal - Brasseur, Philippe (BioMed Central, 2007)
BACKGROUND: There are no data on the long term use of an artemisinin combination treatment in moderate or high transmission areas of Africa. METHODS AND FINDINGS: Artesunate plus amodiaquine (AS+AQ) was used to treat slide-proven Plasmodium falciparum-infected patients of all ages in the Oussouye district, Casamance, Senegal, over a period of six years (2000 to 2005). Efficacy, by Kaplan Meier survival analysis (n = 966), and safety (adverse event rates, n = 752) were determined over 28 days. A weight-based dosing regimen was used for the loose tablets during 2000–2003 (n = 731) and a commercially available co-blister was used during 2004–2005 (n = 235). Annual crude (non PCR corrected) rates remained stable over the study period [range 88.5–96.7%; overall 94.6 (95% CI 92.9–95.9)]. Nine co-blister treated patients (0.9%) withdrew because of drug-related adverse events; seven had gastrointestinal complaints of whom two were hospitalized for vomiting. By Day 28, the mean total bilirubin (n = 72), AST (n = 94) and ALT (n = 95) values decreased. Three patients had Day 28 AST/ALT values > 40 < 200 IU/L. Changes in white cell counts were unremarkable (n = 87). CONCLUSION: AS+AQ in combination was highly efficacious and well-tolerated in this area and justifies the decision to use it as first line treatment. Long-term monitoring of safety and efficacy should continue.